Content analysis of EU directives and regulations: legislative frameworks and consumer rights - Alexandra Gheorghiu; Cosmin Ungureanu (EURINT)
This study analyses the European Union's regulatory frameworks on data protection and consumer rights. It examines landmark legislations such as the General Data Protection Regulation (GDPR), the Data Governance Act (DGA), and others that shape data privacy, digital content management, and consumer protection across the EU. Utilizing Iramuteq software for content analysis, it identifies thematic clusters and relationships within the texts, uncovering core concepts like digital service conformity, consumer rights, and the role of public data governance. Through cluster and factor analysis, the study reveals how these legal instruments collectively promote data security, innovation, and market fairness while ensuring consistent consumer protection and legal compliance throughout EU member states.